Distribution of Arbuscular Mycorrhizal (AM) Fungi in Koochi Hills, Western Ghats, Coimbatore District, Tamil Nadu - Nagarajan, N.; Maheswari, Uma; Mohan, V.; Suresh, S. N. (Indian Forester, 2011)
An attempt has been made to investigate the occurrence and distribution of arbuscular mycorrhizal (AM) fungi in association with the roots and rhizosphere soils of 46 different plant species belonging to 25 families grown in Koochi Hills, Western Ghats, Coimbatore district, Tamil Nadu. It was found that all the samples had AM fungal colonization in the form of vesicular, arbuscular and hyphal structures in the roots and spores from the rhizosphere soils but there was variation in per cent root colonization and soil spore population. Total of 18 different AM fungi belonging to four genera viz., Acaulospora, Gigaspora, Glomus and Scutellospora were recorded from the rhizosphere of different plant species. Among them, the genus Glomus was found most dominant group of AM fungi. In this study, AM fungal association was reported for the first time in some of the plants of the families such as Araceae, Caryophyllaceae, Asteraceae, Chenopodiaceae, Elaeginaceae, Euphorbiaceae, Poaceae, Nyctaginaceae, Oleaceae, Onagraceae, Polygonaceae, and Portulacaceae, which were reported to be non-mycorrhizal.